Flavonoids from Engineered Tomatoes Inhibit Gut Barrier Pro-inflammatory Cytokines and Chemokines, via SAPK/JNK and p38 MAPK Pathways - Tomlinson, Matthew L.; Butelli, Eugenio; Martin, Cathie; Carding, Simon R. (Frontiers in Nutrition, 2017)
Flavonoids are a diverse group of plant secondary metabolites, known to reduce inflammatory bowel disease symptoms. How they achieve this is largely unknown. Our study focuses on the gut epithelium as it receives high topological doses of dietary constituents, maintains gut homeostasis and orchestrates gut immunity. and Ddysregulation leads to chronic gut inflammation, via dendritic cell (DC) driven immune responses. Tomatoes engineered for enriched sets of flavonoids (anthocyanins or flavonols) provided a unique and complex naturally consumed food matrix to study the effect of diet on chronic inflammation. Inflammation assays were used with Pprimary murine colonic epithelial cell based inflammation assays s consisting offor chemokine induction, apoptosis and proliferation and effects on kinase pathways. Primary murine leukocytes and dendritic cellsDCs were used to assay effects on transmigration. A murine intestinal cell line was used to assay wound healing. Engineered tTomato extracts (anthocyanins or flavonols) showed strong and specific inhibitory effects on a set of key epithelial pro-inflammatory cytokines and chemokines. Chemotaxis assays showed a resulting reduction in the migration of primary leukocytes and DCs. Activation of epithelial cell SAPK/JNK and P38 MAPK signaling pathways were specifically inhibited. The epithelial wound healing-associated STAT3 pathway was unaffected. Cellular migration, proliferation and apoptosis assays confirmed wound healing processes were not unaffected by flavonoids. We show flavonoids target epithelial pro-inflammatory kinase pathways, inhibiting chemotactic signals resulting in reduced leukocyte and DC chemotaxis. Thus, both anthocyanins and flavonols modulate epithelial cells to become hyporesponsive to bacterial stimulation. Our results identify a viable mechanism to explain the in vivo anti-inflammatory effects of flavonoids.